Privacy, time consistent optimal labor income taxation and education policy - Kai A. Konrad (Institute for the Study of Labor (IZA), 1999)
Incomplete information is a commitment device for time consistency problems. In the context of time consistent labor income taxation privacy can lead to a Pareto superior outcome and increases the effectiveness of public education as a second best policy.
Keywords: H23; H21; 330; Privacy; commitment; time consistent income taxation; Bildungsinvestition; Lohnsteuer; Optimale Besteuerung; Bildungspolitik; Zeitkonsistenz; Bildungsökonomik; Bildungsertrag; Unvollkommene Information; Theorie